Artisanal-small Scale Mining in Myanmar - Aung Kyin (Applied Environmental Research, 2014)
In many parts of the world, artisanal or small-scale mining activities are at least as important as large-scale mining activities. The numbers of people employed are actually considerably greater than in large companies. In 2002, an estimated 13 million people a large percentage of those are women and children are artisanal and small scale miners operating mainly in developing countries. Although the numbers of small-scale miners and their dependents are estimated at up to 80-100 million people, governments are frequently reluctant to give legal recognition to artisanal miners. This paper discusses approaches to develop the Artisanal–Small Scale Mining (ASM) sector in developing countries. This includes choice of mineral commodity, available technologies and economic/geological criteria. Other considerations include access to finance, area selection, and personnel. The parameters of mineral economic analysis are also essential for a successful ASM mining operation. Finally, choice of mining equipment is critical to success.